BiblioTech why libraries matter more than ever in the age of Google - Palfrey, John G. 1972- (Basic Books, 2015)
"Libraries today are more important than ever. More than just book repositories, libraries can become bulwarks against some of the most crucial challenges of our age: unequal access to education, jobs, and information. In BiblioTech, educator and technology expert John Palfrey argues that anyone seeking to participate in the 21st century needs to understand how to find and use the vast stores of information available online. And libraries, which play a crucial role in making these skills and information available, are at risk. In order to survive our rapidly modernizing world and dwindling government funding, libraries must make the transition to a digital future as soon as possible-by digitizing print material and ensuring that born-digital material is publicly available online. Not all of these changes will be easy for libraries to implement. But as Palfrey boldly argues, these modifications are vital if we hope to save libraries and, through them, the American democratic ideal. "..